Three‐Dimensional Echocardiography Enhances Diagnostic Accuracy of Supramitral Ring. Issue 6 (12th December 2014) - Jone, Pei‐Ni; Bremen, Carlie; DiMaria, Michael; Campbell, David N.; Jaggers, James; Younoszai, Adel; Ivy, D. Dunbar
<x xml:space="preserve">Abstract</x> Real time three‐dimensional echocardiography (RT3DE) allows for accurate morphological characterization of congenital heart disease and complements two‐dimensional (2D) echocardiography. Accurate evaluation of the mitral valve and supramitral ring prior to surgery aids the surgeon in successful resection of the ring and repair of associated mitral valve abnormalities. We report a case of congenital mitral valve stenosis from a supramitral ring in a young child using real time three‐dimensional transesophageal echocardiography.